'Becoming' in Jane Eyre: Charlotte Brontë through the Eyes of Gilles Deleuze. (November 2014) - Posman, Sarah
<x content-type="archive" xml:space="preserve">Abstract</x> In four of his books Gilles Deleuze makes a reference to the Brontës. In Dialogues and A Thousand Plateaus he mentions Charlotte Brontë as an example of literature that surpasses a subject-centred narrative, a literature of what he calls a 'haecceity' or 'thisness', in which events take precedence over subjects making life choices. This essay concentrates on Jane Eyre: An Autobiography in teasing out Deleuze's surprising mentioning of Charlotte Brontë and explores how a Deleuzian 'haecceity'-vantage point can change our understanding of life narratives and authorship.